2013
DOI: 10.5114/pwki.2013.37498
|View full text |Cite
|
Sign up to set email alerts
|

Risk is not flat. Comprehensive approach to multidimensional risk management in ST-elevation myocardial infarction treated with primary angioplasty (ANIN STEMI Registry)

Abstract: IntroductionCurrent risk assessment concepts in ST-elevation myocardial infarction (STEMI) are suboptimal for guiding clinical management.AimTo elaborate a composite risk management concept for STEMI, enhancing clinical decision making.Material and methods1995 unselected, registry patients with STEMI treated with primary percutaneous coronary intervention (pPCI) (mean age 60.1 years, 72.1% men) were included in the study. The independent risk markers were grouped by means of factor analysis, and the appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Data from another study showed that PCI with II-DES is associated with lower risk of clinically meaningful restenosis, stent thrombosis, and a lower risk of death compared with I-DES [21]. Considering that the group of patients with anaemia have a higher risk of death [22], recurrent MI [2], and more common complex atherosclerotic lesions, they are at high risk of restenosis after PCI, which makes the use of DES particularly advantageous in them. study there was increase risk of in-hospital bleeding requiring blood transfusion in patients with anaemia.…”
Section: Left Ventricular Ejection Fractionmentioning
confidence: 99%
“…Data from another study showed that PCI with II-DES is associated with lower risk of clinically meaningful restenosis, stent thrombosis, and a lower risk of death compared with I-DES [21]. Considering that the group of patients with anaemia have a higher risk of death [22], recurrent MI [2], and more common complex atherosclerotic lesions, they are at high risk of restenosis after PCI, which makes the use of DES particularly advantageous in them. study there was increase risk of in-hospital bleeding requiring blood transfusion in patients with anaemia.…”
Section: Left Ventricular Ejection Fractionmentioning
confidence: 99%
“…The trials with worse bleeding outcomes tended to have more additional inclusion bleeding risk factors than those with neutral or improved bleeding outcomes (2 [1][2][3][4] versus 0 [0-2], respectively, p=0.058). The median number of bleeding risk factors for trials with "net harm" tended to be slightly higher than that for the other studies (2 [0-4] versus 0 [0-2], respectively, p=0.1995).…”
Section: Additional Bleeding Hazard Markers and Safety Outcomesmentioning
confidence: 99%
“…We previously introduced a multidimensional risk management concept for ACS [2]. The novel approach differentiates bleeding and hemodynamic hazards allowing conscious management of these contradictory sources of threat.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were consistent with previous studies in literature. [20][21][22][23] In the univariate regression analysis, differently from other variables, hemoglobin, hematocrit, albumin and LVEF were found to be negatively correlated to in-hospital mortality, meaning that lower values in these variables were associated to a higher mortality. However, this association was no longer significant after the multivariate analysis, except for LVEF.…”
Section: -18mentioning
confidence: 99%
“…Nevertheless, little is known about the correlation between the Gensini score and short-term mortality in STEMI patients. [20][21][22][23] There are few recently published studies that have evaluated the Gensini score in the context of P-PCI. In a recent report, the Gensini score was found to be associated with lower MACE during hospital stay and at 6 months after PCI in acute STEMI patients.…”
Section: -18mentioning
confidence: 99%